Peran Activity-Based Costing dalam Akurasi Harga Pokok Produksi dan Kinerja Keuangan Perusahaan yang Terdaftar dalam BEI: Study Kasus PT Mustika Ratu Tbk - Sahriah, Sitti; Janna, Miftahul; Dampangtiro, Ananta Putra; Zalbina, Filya; Susanto, Adnan Dwi; Hasan, Asriani (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
In the modern business environment, characterized by increasingly intense competition and high complexity of production processes, companies listed on the Indonesia Stock Exchange are required to have accurate cost information systems to support pricing decisions and improve financial performance. The use of traditional costing methods that allocate overhead costs in a general manner often leads to cost distortions, particularly in companies with diversified products and varied production activities. This study aims to analyze the role of Activity-Based Costing in improving the accuracy of cost of goods manufactured calculations and its impact on corporate financial performance, using PT Mustika Ratu Tbk as a case study. The research method employed is descriptive quantitative analysis by examining production cost data and the company’s financial performance. The results show that the implementation of Activity-Based Costing produces more accurate cost of goods manufactured calculations compared to traditional methods, as overhead costs are allocated based on activities that consume resources. This cost accuracy minimizes the occurrence of overcosting and undercosting of products, thereby supporting more competitive and realistic pricing. In addition, the application of Activity-Based Costing contributes positively to the company’s financial performance through improved operational efficiency, more effective cost control, and enhanced profitability. From a managerial perspective, this method provides relevant cost information for strategic decision-making, budgeting, and performance evaluation. Thus, Activity-Based Costing is proven to play an important role as an accurate and strategic costing system in supporting the sustainability and competitiveness of manufacturing companies listed on the Indonesia Stock Exchange.